Using Canva for Magazine Preparation: A Case Study on Students' Experiences in Enhancing Writing Skills - Dr K M A AHAMED ZUBAIR (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2025)
Some Arabic language lovers at The New College, University of Madras, Chennai, India, have expressed concerns about their writing skills in Arabic. To address this, they spent their vacation time engaging in writing exercises. This study aims to describe the steps involved in these writing skill exercises and the production of a magazine as a result of these activities. The researcher employed a qualitative research method to gain a comprehensive understanding of the writing exercises. Data was collected through personal interviews with five students, focusing on the task division process, selection of tools used, and other related aspects. The data analysis followed the three steps of the Miles and Huberman model: data display, data reduction, and drawing conclusions. The results indicated that the writing exercises involved dividing the writing topics among five individuals. The topics included university events, daily activities, prominent figures, archives, and photo collections. To facilitate their work, they used Canva for design purposes. Ultimately, they submitted their work to a supervisor for corrections and suggestions. It was found that the students still struggled with certain methods, particularly with paying attention to writing "hamza." Consequently, they published their work via WhatsApp and Instagram.